The Young Suns Exoplanet Survey: Detection of a wide-orbit planetary-mass companion to a solar-type Sco-Cen member. Issue 1 (18th December 2019) - Bohn, A J; Kenworthy, M A; Ginski, C; Manara, C F; Pecaut, M J; de Boer, J; Keller, C U; Mamajek, E E; Meshkat, T; Reggiani, M; Todorov, K O; Snik, F
ABSTRACT: The Young Suns Exoplanet Survey consists of a homogeneous sample of 70 young, solar-mass stars located in the Lower Centaurus-Crux subgroup of the Scorpius-Centaurus association with an average age of 15 ± 3 Myr. We report the detection of a co-moving companion around the K3IV star TYC 8998-760-1 (2MASSJ13251211–6456207) that is located at a distance of 94.6 ± 0.3 pc using SPHERE/IRDIS on the VLT. Spectroscopic observations with VLT/X-SHOOTER constrain the mass of the star to 1.00± 0.02 M_ and an age of 16.7± 1.4 Myr. The companion TYC 8998-760-1 b is detected at a projected separation of 1.71″, which implies a projected physical separation of 162 au. Photometric measurements ranging from Y to M band provide a mass estimate of 14± 3 M_jup by comparison to BT-Settl and AMES-dusty isochrones, corresponding to a mass ratio of q = 0.013 ± 0.003 with respect to the primary. We rule out additional companions to TYC 8998-760-1 that are more massive than 12 M_jup and farther than 12 au away from the host. Future polarimetric and spectroscopic observations of this system with ground and space based observatories will facilitate testing of formation and evolution scenarios shaping the architecture of the circumstellar environment around this 'young Sun'.